The Contestation of Religious Moderation in Digital Da'wah: Study on Buya Syakur and Buya Yahya YouTube Channels - Uswatussolihah, Uus; Zaenab, Siti; Syafriani, Desy (Jurnal Dakwah Risalah, 2024)
This article examines the contestation of religious moderation discourse in da'wah on the YouTube Channels of Buya Syakur and Buya Yahya. Both are clerics from moderate Islamic mass organizations who are known to actively promote religious moderation. This research is a qualitative research with a cyber ethnography approach and text analysis based on Stephen Toulmin's argumentative rhetoric model. Toulmin's argumentative rhetoric combines Claim (C), Data/Ground (D), Warrant (W), Backing (B), Qualifier (Q) and Exception/Rebutta (R). The results of the study indicate that there are different views on the moderation of the concept and discourse of religious moderation and its implementation in national and state life. Buya Syakur discusses moderation as a necessity to create unity and brotherhood amidst the reality of religious and cultural plurality. He recommends a reinterpretation of religious texts. Unlike Buya Syakur, Buya Yahya states that Muslims do not actually need a religious moderation movement, because Islam is a religion that has moderate characteristics since its inception. Buya Yahya actually appealed to Muslims to be aware of the discourse and movement which he feared could damage the peace of Muslims themselves. The difference in views between Buya Syakur and Buya Yahya occurred due to differences in understanding several concepts in the Quran. The difference in views between the two shows the existence of contestation in the preaching of religious moderation. Contestation is commonplace in the digital space. However, this contestation actually enriches the discourse on religious moderation in Indonesia.